Implementation of a pid controller in a dc motor system: a case study on a floor cleaning robot - Nanda, Rizki Aulia; Karyadi, Karyadi; Suhara, Ade; Tukino, Tukino; Guntur, Muhamad (Politeknik Negeri Lhokseumawe, 2025)
A floor-cleaning robot requires a stable and consistent movement to ensure effective cleaning. This study implements a Proportional-Integral-Derivative (PID) control system using Arduino Uno to regulate the DC motor’s speed and rotation. A well-tuned PID system ensures smooth and constant motion, optimizing the cleaning process. Without PID control, the robot’s movement can become inconsistent, reducing its cleaning efficiency. The research focuses on designing and implementing a PID system to achieve constant speed and rotation through programming. The selected PID parameters are Kp = 0.2, Ki = 50, and Kd = 0, effectively making it a Proportional-Integral (PI) controller. Experiments were conducted under two conditions: (1) unloaded motor testing—where the motor’s rotational stability was assessed without external load, and (2) loaded robot operation—where the robot was tested while cleaning a dirty floor. Results showed that the DC motor's unloaded speed was initially 5 RPM, stabilizing at 10.62 RPM. Under load, the robot's speed started at 0.2 RPM, peaked at 6.85 RPM, and maintained an average velocity of 4.85 cm/s. The robot demonstrated consistent motion in forward, left-turn, and right-turn maneuvers, achieving 13-degree rotations in 30 seconds. The robot was able to operate for 30 minutes, maintaining a stable speed between the 3rd and 22nd minute, before declining as battery power depleted. The findings confirm that the implementation of a PI controller effectively stabilizes motor rotation and enhances floor-cleaning efficiency. Additionally, this control method can be adapted to larger-scale robots and various DC/AC motor systems.